2014
DOI: 10.18632/oncotarget.2414
|View full text |Cite
|
Sign up to set email alerts
|

The DNA2 nuclease/helicase is an estrogen-dependent gene mutated in breast and ovarian cancers

Abstract: Genomic instability, a hallmark of cancer, is commonly caused by failures in the DNA damage response. Here we conducted a bioinformatical screen to reveal DNA damage response genes that are upregulated by estrogen and highly mutated in breast and ovarian cancers. This screen identified 53 estrogen-dependent cancer genes, some of which are novel. Notably, the screen retrieved 9 DNA helicases as well as 5 nucleases. DNA2, which functions as both a helicase and a nuclease and plays a role in DNA repair and replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…replication stress caused by the mec1-21 mutation 48 . Interestingly, similar to this observation in yeast cells, studies from our group and others have demonstrated that DNA2 is overexpressed in a broad spectrum of malignancies including breast cancer, ovarian cancer, lung cancer, prostate cancer, glioblastoma, pancreatic cancer, leukemia, colon cancer, melanoma, Lynch Syndrome, and hereditary nonpolyposis colorectal cancer 19,42,45 . DNA2 overexpression is needed for the tolerance of increased replication stress induced by oncogene activation such as H-Ras or cyclin E in osteosarcoma and breast cancer cells, and partial depletion of DNA2 reduces the tumorigenicity of breast cancer cells 42 .…”
Section: Consistent With This Notion Dna2 Is Overexpressed Via Gene supporting
confidence: 65%
“…replication stress caused by the mec1-21 mutation 48 . Interestingly, similar to this observation in yeast cells, studies from our group and others have demonstrated that DNA2 is overexpressed in a broad spectrum of malignancies including breast cancer, ovarian cancer, lung cancer, prostate cancer, glioblastoma, pancreatic cancer, leukemia, colon cancer, melanoma, Lynch Syndrome, and hereditary nonpolyposis colorectal cancer 19,42,45 . DNA2 overexpression is needed for the tolerance of increased replication stress induced by oncogene activation such as H-Ras or cyclin E in osteosarcoma and breast cancer cells, and partial depletion of DNA2 reduces the tumorigenicity of breast cancer cells 42 .…”
Section: Consistent With This Notion Dna2 Is Overexpressed Via Gene supporting
confidence: 65%
“…Loss and overexpression of DNA2 has been observed in human cancers and cancer cell lines125758, while haploinsufficiency promotes cancer formation in heterozygous DNA2 -knockout mice9. This suggests a complex role in cancer, where genome instability caused by impaired DNA2 function may drive tumorigenesis, whereas upregulation of DNA2 may help cancer cells to survive continuous DNA replication stress.…”
Section: Discussionmentioning
confidence: 99%
“…CRYL1 has been shown to regulate G 2 -M phase transition and expression has been linked to patient prognosis [53]. DNA2 is a DNA helicase that plays an important role in processing Okazaki fragments during DNA replication and DNA2 expression has been correlated to patient survival [54]. HJURP is a histone chaperone shown to play a role in the progression of gliomas and breast tumors [55,56].…”
Section: Discussionmentioning
confidence: 99%